A study on problems of bumiputera contractor in construction industry - Mohd Hafis, Othman (2010)
Nowadays, the number of Bumiputera contractors in construction industry Malaysia is increasingly. Based on the data obtained from Pusat Khidmat Kontraktor, the number of Bumiputera contractors exists was more than thirty nine thousand due to the many factors. Hence, this study is addressing the issue. The objectives of this study are to identify the economic growth of construction industry and the factors leading to the increasing number of Bumiputera contractors and also the problems that they encountered in this industry. Apart from literature review on the issues, several questionnaires have been sent out to the Pahang based on Bumiputera contractors of Class A-C. The analysis shows that the increasing numbers of Bumiputera contractor is closely link to the development of the construction industry. The New Economy Policy has also increased the Bumiputera participation in the contracting field. The study shows that the main problems faced by Bumiputera contractors are finance, material, employee and also plants and machineries. Nevertheless, all the problem stated are still under control.